واقع تطبيق الضرائب المؤجلة في الجزائر في ظل متطلبات النظام المحاسبي المالي -دراسة حالة مؤسسة Agrodive- - شوقي, طارق; خلادي, عبد الغني (جامعة الوادي - University of Eloued, 2024)
Deferred taxes are among the topics that still raise a lot of controversy among professionals and academics between what was stated in the international standard IAS12 income taxes and the financial accounting system SCF. The study aims to clarify how the accounting and fiscal treatment of deferred taxes in Algerian economic institutions and the impact of this on their tax burden, through a case study of the AGRODIV Foundation, which is a public economic institution, so that the importance of using the deferred tax technique in calculating the tax burden was reached, as it directly affects it by increase or decrease in the results account table.
The reality of applying deferred taxes in Algeria in light of the requirements of the financial accounting system -AGRODIVE CASE STUDY
مقال
Keywords: الضرائب المؤجلة ; المعيار الدولي IAS12ضرائب الدخل ; النظام المحاسبي المالي ; العبئ الضريبي; Deferred taxes; IAS12; Income taxes; Financial accounting system; Tax burde